Gaming and Digital Technology in Healthcare Training: A Scoping Review of Studies in African Countries - Oluwarotimi Randle; Selvarani Moodley; Dhanashree Pillay (Studies in Learning and Teaching, 2026)
Healthcare training institutions worldwide are under increasing pressure to adopt innovative, scalable, and contextually relevant teaching methods to address gaps in workforce skills and training capacity. The integration of gaming and digital technology into healthcare training has accelerated globally. While these technologies have enhanced interactivity, engagement, and skill acquisition, evidence from African contexts remains fragmented and under-reported. This scoping review addresses this gap by identifying, mapping, and synthesizing published studies on the use of digital gaming and technology for healthcare training across African countries, guided by Arksey and O’Malley’s (2005) scoping review framework and PRISMA guidelines. Findings show a growing body of African research on digital tools such as virtual reality, serious games, mobile applications, and gamified learning platforms, with a significant increase in studies since 2021. The studies encompassed various technologies such as virtual reality, serious games, and mobile apps, applied across. key areas of healthcare. This is the first consolidated overview of how digital gaming and technology are being adopted within healthcare education in Africa. It highlights both the potential of these tools to strengthen training and the need to amplify African-led innovations, foster cross-regional collaboration, and address linguistic and contextual barriers that may limit knowledge sharing.